Classification Of Outpatient Visit Status Walking at Dr. Zubir Mahmud Hospital Using Algoritma C4.5 - Fikria, Putri; Dinata, Rozzi Kesuma; afrillia, Yesy (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to classify the status of outpatient visits at RSUD Dr. Zubir Mahmud into three main categories, namely